Assessing health impacts within environmental impact assessments: An opportunity for public health globally which must not remain missed - Harris, P.; Viliani, F.; Spickett, Jeffery (MDPI AG, 2015)
Within the member states of the United Nations 190 of 193 have regulated Environmental Impact Assessments (EIA) which is a systematic process to prevent and mitigate the potential environmental impacts of industry development projects before these occur. However, the routine and comprehensive assessment of health impacts within EIAs remains underdeveloped. Focusing, as an example, on the risks to global health from the global shift in the mining industry towards Low and Middle Income Countries LMIC), this viewpoint details why connecting with EIA is an essential task for the health system. Although existing knowledge is out of date in relation to global practice we identify how health has been included, to some extent, in High Income Country EIAs and the institutional requirements for doing so. Using arguments identified by industry themselves about requiring a ‘social license to operate’, we conclude that EIA regulations provide the best current mechanism to ensure health protection is a core aspect in the decision making process to approve projects.